Analisis Kesulitan Siswa Kelas 1 Dalam Membaca Permulaan di SDN - Lailatun Nuraniyah; Muh Arafik; Titis Angga Rini; Lailatun Nuraniyah; Muh Arafik (Universitas Negeri Malang, 2022)
Abstract: This study aims to describe the difficulties experienced by grade 1 students in reading the beginning with the SAS method, which includes difficulties in pronouncing sound symbols into sentence forms, word forms, syllables and letter forms. Then, the students' difficulty in synthesizing letters into syllables, syllables into words and words into sentences. The approach used in this study is a qualitative approach with a descriptive type of research. There are 3 data collection techniques used, namely tests, interviews and documentation. Based on the results of the study, it showed that there were 5 students who were classified as having difficulty in reading the beginning. The characteristics of the initial reading difficulties experienced by students are that students are still spelling, stammering, doubting or not confident and mispronouncing a sentence form, word form and syllable form. Then, students have difficulty in distinguishing between one letter and another, so students still have difficulty in combining the arrangement of letters in a syllable, word or sentence. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kesulitan yang dialami siswa kelas 1 dalam membaca permulaan dengan metode SAS, yang mencakup kesulitan dalam pelafalan simbol bunyi menjadi bentuk kalimat, bentuk kata, suku kata dan bentuk huruf. Kemudian, kesulitan siswa dalam mensintesakan huruf menjadi suku kata, suku kata menjadi kata dan kata menjadi kalimat. Pendekatan yang digunakan dalam penelitian ini yaitu pendekatan kualitatif dengan jenis penelitian deskriptif. Terdapat 3 teknik pengumpulan data yang digunakan yaitu tes, wawancara dan dokumentasi. Berdasarkan hasil penelitian menunjukkan terdapat 5 siswa yang tergolong kesulitan dalam membaca permulaan. Karakteristik kesulitan membaca permulaan yang dialami siswa yaitu siswa masih mengeja, terbata-bata, ragu atau tidak percaya diri dan salah dalam melafalkan suatu bentuk kalimat, bentuk kata dan bentuk suku kata. Kemudian, siswa kesulitan dalam membedakan antar satu huruf dengan huruf lainnya, sehingga siswa masih kesulitan dalam menggabungkan susunan huruf dalam suatu suku kata, kata ataupun kalimat.